Internal Party Factionalization and Electoral Performance of Political Parties in Nigeria: An Analysis of APGA in Anambra State - OKAFOR, Uchenna; ALUMONA, Ikenna Mike; ONWUANABILE, Kingsley Maduka (Socialscientia: Journal of Social Sciences and Humanities, 2025)
Political parties across the globe are considered as the building blocks of democracy. Since the return of democracy in 1999, the phenomenon of party factionalisation occasioned by the absence of internal party democracy has been the bane of party politics in Nigeria. This paper basically investigated the impact of internal party factionalisation on electoral performance using the All Progressive Grand Alliance in Anambra state as a focal point of analysis. The paper found out that while internal party fractionalisation has not impacted on the party’s success in the gubernatorial elections in Anambra state, it has continued to rob the party of expected victory in the legislative elections in the state. The party’s performance in the state’s national legislative seats has been abysmal while its control of the state legislature has suffered major electoral setbacks since 2015. The paper recommends that efforts to end the incessant factionalisation of the party and improve the party’s electoral fortunes can only be achieved if the powerful members of the party eschew their neopatrimonial character; ensure that the processes of selecting delegates and candidates for elections reflect the will of the majority.